Free Cash Flow, Leverage, and Firm Value: The Moderating Role of Managerial Ownership - Ade Ermalini; I Dewa Nyoman Badera (Dinasti Publisher, 2025)
The firm value represented by its share price often fluctuates. To select profitable investments, investors must be able to estimate firm value. The purpose of this study is to gather empirical evidence regarding the influence of free cash flow and leverage on firm value, and how managerial ownership moderates this influence. The study population includes all companies listed on the Indonesia Stock Exchange between 2021 and 2023, with a sample of 760 companies and 2,016 observations. Purposive sampling was used to choose the sample. This study uses moderated regression analysis with STATA application. The findings indicate that free cash flow has a positive effect on firm value, while leverage has no effect on firm value. On the other hand, managerial ownership does not play a role in moderating the effect of free cash flow and leverage on firm value.